THE IMPORTANCE OF BREASTFEEDING EDUCATION - Chrásková, Jana; Boledovičová, Mária (Profese Online, 2015)
Background: Breastfeeding and breast milk nutrition is natural and non-substitutable food for a newborn. According to WHO, breast milk is the best food for all babies, including premature born and sick babies. To ensure correct and sufficient breastfeeding it is necessary to provide effective training for mothers.Aim: The aim of this study is to analyze the existing range of educational programs and methods bringing the most impact on exclusive breastfeeding for babies less than six months.Methods: Licensed electronic databases and freely accessible databases were used to obtain the data for the period 2004-2014. Study inclusion criteria covered education methods, breastfeeding support, education efficiency, exclusive breastfeeding for six months. From 38 previously identified studies only 19 studies met the study inclusion criteria.Results: Illustrative and practical methods used in breastfeeding education programs appeared to be the most effective. At the same time it is necessary to pay more attention to the questions and enquiries made by women. Education in the field of breastfeeding should be initiated during the prenatal period to ensure complex education in this area.Conclusion: Sufficient knowledge in the field of breastfeeding helps reduce the risk of various complications and breastfeeding disorders, it also promotes longer period (preferably 6 months) of breastfeeding.Key words: study review, newborn nutrition, midwife, prenatal care, breastfeeding education, breastfeeding support, effectiveness
Keywords: Study review; newborn nutrition; midwife; prenatal care; breastfeeding education; breastfeeding support; effectiveness